Training mediated by Mixed Reality Simulations (MRS) based on the diagnosis of the functioning of the CMCE in Santander (Colombia) - Lozada-Ballesteros, Yeny Carolina; Barrios-Galvis, Sonia Paola (DIXI, 2025)
The research presents the design of training mediated by Mixed Reality Simulations, based on the diagnosis of the functionality of the Municipal School Coexistence Committees (CMCE) in the Department of Santander, Colombia, presenting the theoretical foundations that consolidate the training scenario from a legal, institutional, and pedagogical perspective, combined with a solid epistemological basis and cutting-edge technology. The research was qualitative, with a socio-legal approach. The main results show that training through immersive experiences that replicate real situations in the educational environment encourages the members of the CMCE to appropriate key concepts for its operation, as well as skills for the effective management of conflicts and the promotion of school coexistence, necessary to ensure a culture of peace in schools.